The antibacterial mechanism of compound preservatives combined with low voltage electric fields on the preservation of steamed mussels (Mytilus edulis) stored at ice-temperature - Wang, Kunmei; Wang, Han; Wu, Yue; Yi, Chong; Lv, Yanxia; Luo, Hongyu; Yang, Tao (Frontiers in Nutrition, 2023)
This study examined the effects of compound preservative agents combined with low voltage variable frequencies on the preservation mechanisms of steamed mussels being held in ice-temperature storage. We utilized the method of coefficient variation weighting to calculate the overall scores of steamed mussels stored under different preservation conditions. The protein physicochemical properties of samples, the growth curves of two dominant spoilage bacteria; Bacillus subtilis and Pseudomonas in the mussels as well as the Structural changes of the cell membranes were mensurated.. The results show that compared with the preservative group and the low voltage variable frequency electric field group, the compound preservatives combined with the electric field group had the highest overall score and thus the best preservation effect. Compared with the blank group, the total sulfhydryl content and myogenic fibrin content of the combined group decreased at the slowest rate, 19.46%, and 44.92%, respectively. The hydrophobicity of the protein surface increased by only 5.67%, with the best water retention, indicating that the samples of the combined group had the least protein deterioration in the combined group. The inhibition mechanism of the combined group inhibited the growth of two dominant spoilage bacteria: Bacillus subtilis and Pseudomonas, in the mussels, destroying the integrity of the cell membrane structure and changing the cell morphology. Overall, we found that the combination of the composite preservatives and the low voltage variable frequency electric field can maintain the best quality of steamed mussels during ice-temperature storage and slow down the rate of protein deterioration during storage.This study proposed a new method of mussel preservation, which provides a new idea for the application of low-voltage frequency conversion electric field and compound preservative in the preservation of aquatic products.